A LATE MIOCENE PIPINE FROG FROM THE URUMACO FORMATION, VENEZUELA (Ameghiniana, 2018)
The crown pipids were already diversified in the Late Cretaceous with three major lineages leading to extant Pipa, Hymenochirini, and Xenopodinae. We report an anuran synsacrum from the late Miocene of Corralito (Urumaco Formation, Venezuela) that represents the first fossil Pipa described so far and the first amphibian of Urumaco. The fossil is referred to a large-sized, undetermined Pipa species matching in size and morphology Pipa pipa, currently inhabiting the Amazonian Basin. If confirmed by further remains, the former presence of an Amazonian taxon at Urumaco would fit with palaeoenvironmental reconstructions indicating a former northward extension of the Amazonian forest.